Origins of the Canadian Association for the Study of the Liver: A Personal Memoir - Jerome B Simon (Canadian Journal of Gastroenterology)
The Canadian Association for the Study of the Liver (CASL) (Association Canadienne Pour L’Étude Du Foie) is a thriving organization. Although it was established more than a quarter of a century ago and has been successful since the beginning, most members are unaware of how CASL came into being or of its humble origins as a precursor club in the 1970s. The present article reviews those early days. It is written as a memoir because of the author’s personal involvement and is based on detailed records, correspondence and handwritten notes from that era.